Tracing notochord-derived cells using a Noto-cre mouse: implications for intervertebral disc development - Matthew R. McCann; Owen J. Tamplin; Janet Rossant; Cheryle A. Séguin (The Company of Biologists, 2012)
SUMMARY Back pain related to intervertebral disc degeneration is the most common musculoskeletal problem, with a lifetime prevalence of 82%. The lack of effective treatment for this widespread problem is directly related to our limited understanding of disc development, maintenance and degeneration. The aim of this study was to determine the developmental origins of nucleus pulposus cells within the intervertebral disc using a novel notochord-specific Cre mouse. To trace the fate of notochordal cells within the intervertebral disc, we derived a notochord-specific Cre mouse line by targeting the homeobox gene Noto. Expression of this gene is restricted to the node and the posterior notochord during gastrulation [embryonic day 7.5 (E7.5)-E12.5]. The Noto-cre mice were crossed with a conditional lacZ reporter for visualization of notochord fate in whole-mount embryos. We performed lineage-tracing experiments to examine the contribution of the notochord to spinal development from E12.5 through to skeletally mature mice (9 months). Fate mapping studies demonstrated that, following elongation and formation of the primitive axial skeleton, the notochord gives rise to the nucleus pulposus in fully formed intervertebral discs. Cellular localization of β-galactosidase (encoded by lacZ) and cytokeratin-8 demonstrated that both notochordal cells and chondrocyte-like nucleus pulposus cells are derived from the embryonic notochord. These studies establish conclusively that notochordal cells act as embryonic precursors to all cells found within the nucleus pulposus of the mature intervertebral disc. This suggests that notochordal cells might serve as tissue-specific progenitor cells within the disc and establishes the Noto-cre mouse as a unique tool to interrogate the contribution of notochordal cells to both intervertebral disc development and disc degeneration.